Schmallenberg Virus in Belgium: Estimation of Impact in Cattle and Sheep Herds. Issue 1 (29th April 2015) - Poskin, A.; Méroc, E.; Behaeghel, I.; Riocreux, F.; Couche, M.; Van Loo, H.; Bertels, G.; Delooz, L.; Quinet, C.; Dispas, M.; Van der Stede, Y.
Summary: Schmallenberg virus (SBV) emerged during summer 2011. SBV induced an unspecific syndrome in cattle and congenital signs (abortions, stillbirths and malformations) in domestic ruminants. To study the impact of SBV in Belgium, a phone survey was conducted upon September 2012. Hereto two groups of cattle farmers (A and B) and two groups of sheep farmers (C and D) were randomly selected. Farms from groups A ( n  = 53) and C ( n  = 42) received SBV‐positive result at RT‐PCR in the Belgian National Reference Laboratory (NRL). Farms from groups B ( n  = 29) and D ( n  = 44) never sent suspected samples to NRL for SBV analysis but were however presumed seropositive for SBV after the survey. Questionnaires related to reproduction parameters and clinical signs observed in newborn and adult animals were designed and addressed to farmers. As calculated on a basis of farmers' observations, 4% of calves in group A and 0.5% in group B were reported aborted, stillborn or deformed due to SBV in 2011–2012. The impact as observed by sheep farmers was substantially higher with 19% of lambs in group C and 11% in group D that were reported aborted, stillborn or deformed due to SBV in 2011–2012. Interestingly, abortions or stillbirths were not clear consequences of SBV outbreak in cattle farms, and the birth of a deformed animal was an essential condition to suspect SBV presence in cattle and sheep farms. This study contributes to a better knowledge of the impact of the SBV epidemic. The results suggest that SBV impacted Belgian herds mostly by the birth of deformed calves, stillborn lambs and deformed lambs. This work also demonstrates that the birth of a deformed calf or lamb was a trigger for the farmer to suspect the presence of SBV and send samples to NRL for further analyses.